2017
DOI: 10.1055/s-0037-1606190
|View full text |Cite
|
Sign up to set email alerts
|

The Lupus Anticoagulant Paradox

Abstract: Lupus anticoagulant (LA) represents the most enigmatic antibody population in patients with antiphospholipid syndrome and represents a paradox that is still unsolved. This class of antiphospholipid antibody causes a phospholipid-dependent prolongation of the clotting time but is associated with an increased risk of thrombosis and pregnancy morbidity. In this review, we will provide an overview of the different antibodies that have been associated with LA activity, their importance based on clinical studies, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 69 publications
1
24
0
Order By: Relevance
“…21 One patient was positive for the lupus anticoagulant, which has been shown to increase the prothrombin time in vitro but paradoxically cause more thrombotic events in vivo. 33 There has been some controversy over the use of anti-Xa measurements on whether it should guide the proper dosing of LMWHs. An adult study has shown that attaining therapeutic anti-factor Xa did not predict either thrombosis or hemorrhage; however, it may still be preferred over prothrombin time or partial thromboplastin time for monitoring therapy.…”
Section: Enoxaparinmentioning
confidence: 99%
“…21 One patient was positive for the lupus anticoagulant, which has been shown to increase the prothrombin time in vitro but paradoxically cause more thrombotic events in vivo. 33 There has been some controversy over the use of anti-Xa measurements on whether it should guide the proper dosing of LMWHs. An adult study has shown that attaining therapeutic anti-factor Xa did not predict either thrombosis or hemorrhage; however, it may still be preferred over prothrombin time or partial thromboplastin time for monitoring therapy.…”
Section: Enoxaparinmentioning
confidence: 99%
“…Even after decades of appearance, the identity of the responsible antigens still remains unsolved. 40 With the consideration of the citrated plasma availability, we were able to perform the LA testing on 70 case patients, of which 30 were from the sporadic miscarriage group and 40 were from the RPL group.…”
Section: Ta B L E 3 Statistical Comparison Of Autoantibodies By Chi-smentioning
confidence: 99%
“…Lupus anticoagulant (LA) is an antiphospholipid antibody that binds phospholipids and proteins associated with the cell membrane (1). Phospholipids are essential in vivo because of their biological role in cell membranes and are used in vitro to accelerate coagulation.…”
Section: Introductionmentioning
confidence: 99%